Gorham-Stout disease of the malleolus: a rare case report - Chuanxi Zheng; Fan Tang; Li Min; Yong Zhou; Yi Luo; Chongqi Tu; Shiquan Zhang (BMC Musculoskeletal Disorders, 2019)
Abstract Background Gorham-Stout disease, also known as vanishing bone disease, idiopathic massive osteolysis, is a rare entity of unknown etiopathology. This disease is characterized by destruction of osseous matrix and proliferation of lymphatic vascular structures and associated with massive regional osteolysis. It has a variable clinical presentation and is commonly considered as a benign disease with a progressive tendency and an unpredictable prognosis. The diagnosis is made by exclusion and based on combination with histological, radiological, and clinical features. Despite that several therapeutic options have shown certain efficacy, the effective treatment still remains controversial and there is no standard treatment to be recommended. Case presentation A previously healthy 40-year-old man presented with right lateral malleolus pain after an ankle sprain and was referred to our hospital. The radiographs indicated rapid massive bone destruction in the distal right lateral malleolus with an unclear margin. Based on the combination with histological, radiological, and clinical features, the diagnosis of Gorham-Stout disease was made. Considering that the residual function of malleolus had to be protected, prior bisphosphonate was used to control the progression of lesion, followed by surgical resection and biological reconstruction with autologous fibular bone grafting. The patient was followed up 8 years after surgery, he presented without progression and recurrence. Conclusions We depict a case of Gorham-Stout disease at the right lateral malleolus and was successfully controlled by medication and surgical intervention. Based on the prior effective medical treatment, resection with biological reconstruction is a useful approach to treat Graham-Stout disease in bone.